Targeting the Inflammasome: A cure for Alzheimer’s disease? - Milner, Mark (Trinity Student Medical Journal, 2017)
Alzheimer’s disease is the most common neurodegenerative disease in the world. Despite years of intense research, its pathogenesis remains quite controversial. Many different explanations have been proposed to describe its onset, the most established of which is the β-amyloid hypothesis. This hypothesis proposes that the disease is primarily caused by the formation of β-amyloid plaques in the brain. The presence of these plaques, it is suggested, ultimately leads to neuroinflammation, tau aggregation and, eventually, neuronal death and the often-cited neurocognitive sequelae observed in Alzheimer’s patients. However, recent evidence suggests neuroinflammation may in fact be a root cause of the disease as opposed to acting as an eventual or coincidental manifestation. More specifically, it has been found that the activation of inflammasomes in microglia (the brains immune cells) contributes to the production of proinflammatory cytokines which then potentiates the neuroinflammatory response, with other downstream affects including increased β-amyloid plaque build-up, tau aggregation and a loss in cognitive function. There- fore, more and more studies are suggesting that neuroinflammation - and particularly the inflammasome - could be targeted therapeutically to prevent and treat Alzheimer’s disease in patients.